Оцінка токсичності та генотоксичності меланіну на тест-системі Drosophila melanogaster - Проценко, О.В.; Дудка, О.А.; Козерецька, І.А.; Фалалєєва, Т.М.; Берегова, Т.В.; Остапченко, Л.І. (Фактори експериментальної еволюції організмів, 2016)
Aim. Melanin is a broad term for a group of natural pigments found in most organisms. Melanin neutralizes the effect
of products of lipid peroxidation and takes part in neurotransmitter processes under numerous pathological processes
damaging functional neuron structures. Experimental data cannot often account for the mechanisms of melanin action
and therefore systematic analysis of all the data published on melanin pigments is necessary for possible employment of
melanins for the pharmacological needs. In the present study, we examined the toxic and genotoxic effects of melanin in
Drosophila melanogaster. Methods. To study the toxicity of melanin determined it was analyzed survival, development
time and fecundity of flies. For study we used the strain mei-9a mei-41D5 / FM7c; mwh, for the detection of repairable DNA
damage in somatic cells, it was employed to determine the genotoxic effects of melanin. Results. Results obtained in the
control and experiment with the addition of melanin was not significantly differ. Conclusions. The ability of melanin,
obtained by yeast Nadsoniella nigra strain Х1-М, cause toxic and genotoxic effects at the model organism Drosophila
melanogaster was evaluated. As a result we demonstrated that the melanin, did not have the toxic or genotoxic effects on
D. melanogaster in concentration 3.5 mg/100 ml.
Keywords: melanin, toxicity, genotoxicity, Drosophila melanogaster.